A case-report of delayed repositioning of intruded permanent maxillary central incisors accompanied by complicated crown fractures: A 2-year follow-up - Azade Rafiee; Hamid Moradian; Maryam Ayatollahi (Wolters Kluwer Medknow Publications, 2016)
Intrusive luxation is the most severe type of dental injury with a complex healing sequence. Pulp necrosis, root resorption (surface, inflammatory and replacement resorption), and defects in marginal periodontal bone healing are the main complications. Treatment strategies can be either active, by repositioning (surgical or orthodontic extrusion), or passive, by spontaneous re-eruption based on the thorough evaluation of the case. This paper reports a case of delayed repositioning of severely intruded permanent maxillary central incisors accompanied by complicated crown fractures after 3 months. After thorough clinical and radiographic evaluations, and based on guidelines, the teeth were surgically repositioned and splinted for 6 weeks. One week after the initial intervention, the endodontic treatment for both permanent maxillary incisors were initiated using calcium hydroxide. 6 months later, the teeth were ready for MTA plug and gutta-percha root canal filling. During the follow-up period, the teeth had remained functional and esthetically acceptable. Further yearly observations are planned at least for 5 years.